An Energy Management System in Smart Classroom Using CupCarbon Simulator - Sulistiawati, Irrine Budi; Soetedjo, Aryuanto; Susanti, Debby Budi; Sukowiyono, Gaguk (Engineering, Technology & Applied Science Research, 2025)
A smart classroom involves integrating smart materials, smart communication and participation, smart evaluation, and smart physical surroundings to enhance the teaching and learning process. One key feature is the Energy Management System (EMS), which aims to reduce the energy consumption in the classroom. This paper proposes an EMS for a smart classroom using the CupCarbon Wireless Sensor Network (WSN) simulator. The study simulates WSN protocols—WiFi, Zigbee, and LoRa—on a campus building at the National Institute of Technology (ITN) Malang, Indonesia, which provides essential communication infrastructure for the EMS. The EMS algorithm controls the operation of the lighting and Air Conditioner (AC) in the classroom based on the occupancy and outdoor temperature. The EMS algorithm is easily implemented on the CupCarbon simulator. The results from five days of simulation show that the LoRa protocol with the mediator achieves the highest energy efficiency in the WSN at 67.93%. The occupancy-based evaluation method also results in a significant energy reduction of 51.55%.